Heteroptera of Slovenia, IV - Gogala, Andrej (Annales. Series historia naturalis, 2007)
Species of the superfamilies Aradoidea, Lygaeoidea and Pyrrhocoroidea occurring in Slovenia are listed and data on the examined specimens presented. Six species or subspecies are reported for Slovenia for the first time: Aradus pallescens frigidus Kiritshenko, 1913, Ischnocoris hemipterus (Schilling, 1829), Stygnocoris cimbricus (Gredler, 1870), Stygnocoris fuligineus (Geoffroy, 1785), Stygnocoris matocqi Péricart, 1993 and Rhyparochromus sanguineus (Douglas & Scott, 1868). As far as the last species is concerned, however, the author believes that it is only a synonym for Rh. phoeniceus. 9 species, previously reported for Slovenia, have been omitted from the list due to misidentifications or misinterpreted localities.
Keywords: biologija; biology; favna; Heteroptera; Pentatomomorpha; Slovenia; Slovenija